An improved moth‐flame optimization algorithm for solving optimal power flow problem - Taher, Mahrous A.; Kamel, Salah; Jurado, Francisco; Ebeed, Mohamed (International transactions on electrical energy systems, 2019)
Summary This paper proposes an improved moth flame optimization (IMFO) algorithm to effectively solve the optimal power flow (OPF) problems. The concept of moth flame optimization (MFO) is inspired from the movement of moth towards the moon direction. IMFO is mainly based on the concept of MFO with modifying the path of moths in new spirals around the flame. Standard IEEE 30‐bus, IEEE 57‐bus and IEEE 118‐bus test systems are used to validate and prove the efficiency and robustness of IMFO algorithm. The validation of the proposed algorithm is based on 15 case studies in terms of different single and multi‐objective functions: fuel cost minimization, gas emission reduction, active power loss minimization, voltage profile improvement, and voltage stability enhancement. The simulation results of the proposed algorithm are compared with those obtained by other well‐known optimization techniques. The obtained results demonstrate the capability and robustness of IMFO algorithm to solve OPF problems. The results reveal that IMFO algorithm is capable of finding precise and better OPF solutions compared with the other techniques. A comparison among the convergence characteristics of IMFO technique and the other techniques proves the prevalence of IMFO to attain the optimal power flow solution with fast convergence.